Dynamic Susceptibility of Skyrmionic Bubbles Stabilized in the Absence of Dzyaloshinskii-Moriya Interaction in Cylindrical Nanostructures - Escrig-Murua, J; Tejo-Lazo, F; Saavedra-Díaz, E (American Institute of Physics, 2019)
The magnetic dynamic susceptibility of cobalt dots hosting a skyrmionic bubble has been obtained by means of micromagnetic simulations by exciting the system with a magnetic field pulse. When the pulse is applied parallel to the dot axis, a single resonance peak is obtained, whereas when the pulse is applied perpendicular to the dot axis, multiple peaks are obtained. The origin of each of these peaks and their evolution as a function of uniaxial anisotropy are studied in detail. The results presented in this work are important in view of the possible realization of tunable frequency devices, since we showed that it is possible to adjust a set of frequencies of skyrmionic bubbles by controlling the uniaxial anisotropy constant of the dot and the direction in which the magnetic pulse is applied. © 2019 Author(s).